Effect of "Tong Du Tiao Shen" Acupuncture Therapy Combined with Rehabilitation Training on the Recovery of Lower Limb Motor Function after Ischemic Stroke - ZHANG Junyu; HAN Wei; JIN Zikai; YANG Kun; HE Chenggong; DAI Fei (康复学报)
ObjectiveTo compare the therapeutic effect of "Tong Du Tiao Shen" acupuncture therapy combined with rehabilitation training of lower limbs and simple rehabilitation training on patients with lower limb dyskinesia after ischemic stroke.MethodsA total of sixty patients were randomly divided into control group (30 patients, 3 cases of detachment) and observation group (30 patients, 3 cases of detachment). The control group took 100 mg aspirin enteric-coated tablets orally once a day, and atorvastatin calcium tablets at 20 mg once at nights, combined with rehabilitation training of lower limbs, including muscle strength training, joint mobility training, weight reduction walking training and balance function training. The training sessions were performed once a day, for 30 minutes and the treatment was performed 6 times a week. In addition to the treatment of the control group, the observation group was also treated with "Tong Du Tiao Shen" acupuncture therapy, taking Baihui, Fengfu, Dazhui, bilateral Fengchi, Yintang, bilateral sun and gutters, applying the method of reinforcing and reducing, keeping the needle for 30 minutes, treating the needle once a day, 6 times a week, four weeks for one course. Both groups were treated for 4 weeks and evaluated with the Fugl-Meyer assessment (FMA), Berg balance scale (BBS), modified Barthel index (MBI) and functional ambulation category (FAC) before and after treatment.ResultsThe differences were not statistically significant in the grade of FMA, BBS, MBI and FAC between the two groups before treatment (P>0.05). After four weeks of treatment in the two groups, all indexes were statistically significant compared to those before treatment (P<0.05). After four weeks of treatment, the grade of FMA, BBS, MBI and FAC in the observation group were reported to be (24.93±5.56) (42.35±4.37) (47.21±6.47) (3.28±1.04), it was better than those in the control group (21.93±4.29) (38.77±5.63) (34.58±4.91) (2.63±1.15). The differences were statistically significant (P<0.05). It indicated that the lower limb function, balance function, activity of daily living ability and walking function were improved in the two groups after treatment, and the degree of improvement in the observation group was better than that in the control group. The difference was statistically significant when comparing the efficacy of the two groups (P<0.05).ConclusionThe therapeutic effect of the "Tong Du Tiao Shen" acupuncture therapy combined with rehabilitation training after ischemic stroke is better than simple rehabilitation training, which is of great significance to the recovery of lower limb function and the improvement of self-care ability.